Shot Peening Induced Corrosion Resistance of Magnesium Alloy WE43. (September 2022) - Patil, T.; Karunakaran, R.; Bobaru, F.; Sealy, M.P.
Abstract: Mechanical surface treatments like shot peening provide a pathway to stabilize degradation of magnesium alloys without compositional change. The resultant subsurface grain refinement, twin dislocations, and nanoprecipitation improves fatigue life but lowers corrosion resistance of magnesium. The lower corrosion resistance is justified by an increase in surface roughness after shot peening. However, a skewed estimate of surface area is expected to justify the inconsistent corrosion behavior of shot peening magnesium compared to other mechanical surface treatments. The objective of this research was to understand the influence of surface topography due to shot peening on the corrosion kinetics of a magnesium alloy WE43. Results showed that the corrosion resistance increased after shot peening WE43 when using an adjusted surface area that better accounts for the topographical features under exposure to corrosion attack.